2006
DOI: 10.1149/1.2356190
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hydrogen Fuel Contaminates on Long-Term PMFC Performance

Abstract: We have studied the effects of H2S and fuel impurity mixtures on hydrogen polymer fuel cell performance. The tests included a range of H2S concentrations, exposure times, and multiple impurity mixtures at various operating conditions such as cell voltage and times of exposure. Analytical methods included fuel cell polarization experiments, cyclic voltammetry, and effluent water and gas analysis using specific ion sensor probes. H2S concentrations as low as 10 ppb, produced negative effects on fuel cell perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
36
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 7 publications
0
36
0
Order By: Relevance
“…Unfortunately, even traces of impurities can have detrimental effects on FC performance (1). For fuel impurities, extensive research has been done on CO poisoning, but much less attention has been given to the effects of H 2 S. We have reported that concentrations of H 2 S as low as 10 ppb (10/10 9 ) caused significant losses after 1000 hour of anode exposure (2). FC tolerance to H 2 S depends on several factors, such as impurity concentration, time of exposure and other operational conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, even traces of impurities can have detrimental effects on FC performance (1). For fuel impurities, extensive research has been done on CO poisoning, but much less attention has been given to the effects of H 2 S. We have reported that concentrations of H 2 S as low as 10 ppb (10/10 9 ) caused significant losses after 1000 hour of anode exposure (2). FC tolerance to H 2 S depends on several factors, such as impurity concentration, time of exposure and other operational conditions.…”
Section: Introductionmentioning
confidence: 99%
“…3 and references therein, for example]. Past H 2 S studies indicate S-species as much stronger site blockers than CO because of a greater affinity for metals, with higher concentrations and longer exposure times capable of leading to irreversible poisoning [4,5,6]. Most recently, we have reported that H 2 S concentrations as low as to ppb, produced negative effects on fuel cell performance [4J.…”
Section: Iatroduetiodmentioning
confidence: 99%
“…Nafion properties depend on various impurities in the system. For example, it was shown in [ 6 ] that additions of H 2 S of about 10 ppb to pure hydrogen resulted in a significant decrease in the proton conductivity through a polymer membrane in a hydrogen fuel cell, i.e., to a decrease in the fuel cell efficiency.…”
Section: Introductionmentioning
confidence: 99%